THE CHALLENGES FOR IMPLEMENTING SMART CITIES IN EMERGING COUNTRIES - Ferreira, Matheus Müller Batista; Ferreira, Érica Damasceno (Editora Impacto Científico, 2025)
This article addresses the main challenges for the implementation of smart cities in emerging countries, focusing on the Brazilian context. Based on a bibliographic, applied, descriptive, and qualitative research approach to identify, describe, and interpret critical factors on the topic, the study examines historical aspects of cities, the right to the city, the evolution of the internet in the country, and concepts of smart cities. The study identifies that the adoption of digital technologies can improve the quality of life, increase the efficiency of public services, and strengthen economic development. However, urban transformation faces significant barriers, such as high infrastructure investment costs, technological limitations, low data integration, government budgetary constraints, and social inequality. The results also highlight the importance of governance models that encourage public-private partnerships, sustainability, and citizen participation. It is concluded that emerging countries, although having the potential to advance, are still moving slowly in the implementation of these solutions, making it essential to strengthen public policies and financing strategies that make cities smarter, more inclusive, and sustainable.DOI: https://doi.org/10.56238/edimpacto2025.071-002